Association between the lactate-to-albumin ratio (LAR) index and risk of acute kidney injury in critically ill patients with sepsis: analysis of the MIMIC-IV database - Yiming Hua; Yiming Hua; Ning Ding; Ning Ding; Huaizhi Jing; Huaizhi Jing; Yifei Xie; Yifei Xie; Hao Wu; Hao Wu; Yue Wu; Yue Wu; et al. (Frontiers in Physiology)
BackgroundLactate-to-albumin ratio (LAR) is an emergency predictive indicator of sepsis-related mortality. An elevated LAR is associated with poor outcomes in critically ill patients. However, its predictive value for acute kidney injury (AKI) in patients with sepsis remains unclear. Therefore, this study aimed to investigate the relationship between LAR and AKI in patients with sepsis.MethodsThe study population was derived from the Medical Information Mart for Intensive Care-IV (2.0) database and stratified into quartiles based on the LAR. The primary endpoint was the occurrence of AKI. The secondary endpoints were the use of renal replacement therapy (RRT) and in-hospital mortality. Kaplan–Meier survival analysis and Cox proportional hazards models were used to assess the association between the LAR index and risk of AKI in patients with sepsis.ResultsIn this study, 5,222 patients with sepsis were included, of whom 3,029 were male (58%). Kaplan–Meier survival analysis demonstrated significant differences in the cumulative incidence of AKI and cumulative usage rate of RRT among patients with sepsis based on the quartiles of the LAR index. Additionally, Cox proportional hazards analysis adjusted for confounding factors showed a significant association between the LAR index and incidence of AKI in patients with sepsis.ConclusionOur study indicated that a high LAR index can serve as an independent predictor of AKI in patients with sepsis.